Vasodilator agents improve hemodialysis vascular access patency: A population-based study from Korea. Issue 40 (8th October 2021) - Kim, Do Hyoung; Han, Donghoon; Kim, Jaehwan; Park, Hayne Cho; Lee, Young-Ki; Shin, Dong Geum; Kang, Min-Kyung; Cho, Jung Rae; Choi, Seonghoon; Lee, Namho
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Vascular access (VA) failure is an important problem for patients undergoing hemodialysis, and maintaining VA patency is challenging. In this study, we used a nationwide database to investigate the effects of nitrate, as a vasodilator, on VA failure in hemodialysis patients. We investigated the Korean insurance claims data of hemodialysis patients who underwent angioplasty for VA failure between January 2012 and December 2017. The patients were divided into 2 groups: those not receiving vasodilator therapy (controls) and those receiving any vasodilator administration (vasodilator treatment, VDT). The primary endpoint was VA primary patency, defined as the time between arteriovenous dialysis access creation and the first percutaneous transluminal angioplasty (PTA). During the study period, a total of 6350 patients were recruited, 409 (6.4%) patients assigned to the VDT group and 5941 (93.6%) controls. PTA was performed in 998 patients (15.7%), including 8 in the VDT group and 990 controls. The VA site PTA rate was significantly lower in the VDT group (2.0%) than in the control group (16.7%, P < .001). In the subgroup analysis, the patency rates associated with the different vasodilators were similar ( P = .736). All vasodilators, except molsidomine, improved the patency rate by approximately 20%. In this large national database study, vasodilator administration was associated with higher VA primary patency, compared with controls, in hemodialysis patients. VDT may have a beneficial effect on maintaining VA patency in patients undergoing hemodialysis.